Country-Wide Analysis of Systemic Factors Associated With Acute Ischemic Stroke Door to Needle Time - McVerry, Ferghal; Hunter, Annemarie; Dynan, Kevin; Matthews, Maureen; McCormick, Michael; Wiggam, Ivan; Vahidassr, Djamil; McErlean, Fintan; Stevenson, Mike; Hopkins, Emer; McKee, Jacqueline; Kelly, James; et al. (Frontiers in Neurology, 2019)
Objective: Pre-hospital, in-hospital and patient factors are associated with variation in door to needle (DTN) time in acute ischemic stroke (AIS). Publications are usually from large single centers or multicenter registries with less reporting on national results. Materials and methods: All AIS patients treated with intravenous tissue plasminogen activator (iv-tPA) over 4 years (2013-2016) in Northern Ireland were recorded prospectively, including patient demographics, pre-hospital care, thrombolysis rate and DTN time. Logistic regression was performed to identify factors associated with DTN time. Results: 1201 patients from 10556 stroke admissions (11.4%) were treated with iv-tPA. Median NIHSS was 10 (IQR 6-17). Median DTN time was 54 minutes (IQR 36-77) with 61% treated < 60 minutes from arrival at hospital. National thrombolysis numbers increased over time with improving DTN time (P=0.002). Arrival method at hospital (ambulance OR 2.3 CI1.4-3.8) pre-alert from ambulance (pre-alert OR =5.3 CI3.5-8.1) and time of day (out of hours, n=650, OR 0.20 CI 0.22-0.38) all P<0.001, were the independent factors in determining DTN time. Variation in DTN time between centers occurred but was unrelated to volume of stroke admissions. Conclusion: Ambulance transport with pre-hospital notification and time of day are associated with shorter DTN time on a national level. Most thrombolysis was delivered outside of normal working hours but these patients are more likely to experience treatment delays. Re-organisation of stroke services at a whole system level with emphasis on pre-hospital care and design of stroke teams are required to improve quality and equitable care in AIS nationally.